Metabolomic effects of intrauterine meloxicam perfusion on histotroph in dairy heifers during diestrus - Zhang, Beibei; Han, Yuan; Cheng, Ming; Yan, Longgang; Gao, Kangkang; Zhou, Dong; Wang, Aihua; Lin, Pengfei; Jin, Yaping (Frontiers in Veterinary Science, 2025)
In ruminants, conceptus elongation is a crucial developmental process that depends on uterine lumen fluid (ULF) and coincides with a period of high pregnancy loss. Prostaglandins (PGs) play indispensable roles in conceptus elongation and implantation. However, the effects of uterus-derived PGs on the uterine environment remain unclear. To explore the metabolic pathways and metabolites induced by endometrium-derived PGs that may affect conceptus elongation and implantation in dairy cows, we investigated the biochemical composition of ULF following intrauterine perfusion of meloxicam from days 12 to 14 of the estrous cycle. Intrauterine administration of meloxicam significantly downregulated the prostaglandin-related metabolites in the ULF. A total of 385 distinct metabolites, primarily clustered within lipids and lipid-like molecules, organic acids and derivatives, organoheterocyclic compounds, and benzenoids, were identified. The metabolite network analysis identified 10 core metabolites as follows: S-adenosylhomocysteine, guanosine, inosine, thymidine, cholic acid, xanthine, niacinamide, prostaglandin I2, 5-hydroxyindoleacetic acid, and indoleacetaldehyde. The pathway enrichment analysis revealed three significantly altered metabolic pathways: arachidonic acid metabolism, tryptophan (Trp) metabolism, and linoleic acid metabolism. A total of five metabolites—guanosine, inosine, thymidine, butyryl-l-carnitine, and l-carnitine—were associated with attachment and pregnancy loss and could serve as predictors of fertility. This global metabolic study of ULF enhances our understanding of histotroph alternations induced by uterus-derived PGs during diestrus in dairy cows, with implications for improving dairy cow fertility.